Effect of General Cooling on Rat Behaviour in â€œOpen Fieldâ€ Test - Lomako, V. V.; Shilo, A. V. (Problems of Cryobiology and Cryomedicine, 2009)
The effect of general cooling on behaviour structure of active and passive rats of different age in â€œopen fieldâ€ test has been studied. General cooling was realised by modified Porsolt method (â€œforced swimmingâ€, FS) in cold water (1ËšÐ¡) and by Bakhmetâ€™ev-Andjus-Gaja one (â€œclose tankâ€, CT). Regardless on cooling type, rat age and psychosomatic type (active or passive one), the dynamics of behaviour structure was shown as having a similar direction: decreased number of active behaviour forms (horizontal and vertical locomotor activity) and predomination of passive behaviour ones (motion in place, sitting, sniffing, rest period increase). At the same time in old passive rats after general cooling in FS and CT tests and movement in young active ones after general cooling in CT, a kind of substitution of all behaviour acts (except grooming in active rat groups) with drowsiness occurred. Ethological analysis has shown the old passive and old active rats to be the less and most resistant to all applied general cooling ways, correspondingly. Young rats were more resistant only to cooling in â€œforced swimmingâ€ test in cold water.